SETTLEMENT OF LAND RIGHTS CERTIFICATE CANCELLATION BASED ON IMPLEMENTATION OF COURT DECISIONS WHICH HAVE PERMANENT LEGAL ENFORCEMENT - Angela Merici Intan Permatasari (INTELIGENSIA MEDIA, 2022)
To achieve legal certainty and legal protection of land rights, a certificate of land rights is given as proof of a person's ownership of a land and its buildings. Certificates are strong evidence, but are not absolute, meaning that at any time they can be sued by other parties through the courts, as long as it can be proven otherwise the physical data and juridical data contained therein must be accepted as correct data. The cancellation of this certificate occurs because of a defect in administrative law in its issuance, or carrying out a court decision that has permanent legal force. This cancellation aims to provide legal certainty regarding the control, ownership, useand utilization of land in Indonesia. The purpose of this study is to analyze the juridical settlement of the implementation of the cancellation of land rights certificates based on the implementation of court decisions that have permanent legal force and to examine andanalyze the obstacles and solutions in implementing court decisions that have permanent legal force. This type of research is empirical legal research. The location of the research was conducted at the Land Office of Klaten Regency. The sampling technique used is the purposive sampling. Data collection techniques in this research are literature study and interviews. The results of this study are the implementation of the cancellation of a certificate that already has legal force is still carried out in accordance with the regulations that were then in effect. There were several obstacles, both from the directapplicant and from the Klaten Regency Land Office.